(untitled) (Homoeopathy for All, 2024)
Loss of appetite is not feeling hungry or having a desire to eat. Child may experience a loss or decrease in appetite during times of slower growth or for a variety of other reasons. Most of the time, an occasional loss of appetite is nothing to worry about. If child appears to be losing weight or talking about wanting to be thinner, then special care should given for these child’s. These can be signs of a physical illness, or anorexia, a condition that often requires both physical treatment and counseling to resolve. Parents can try several approaches to help their child regain his appetite.